Bacillus thuringiensis Vip1 Functions as a Receptor of Vip2 Toxin for Binary Insecticidal Activity against Holotrichia parallela - Jianxun Geng; Jian Jiang; Changlong Shu; Zeyu Wang; Fuping Song; Lili Geng; Jiangyan Duan; Jie Zhang (Toxins, 2019)
Bacillus thuringiensis is a well-known entomopathogenic bacterium that produces vegetative insecticidal proteins (Vips, including Vip1, Vip2, Vip3, and Vip4) during the vegetative phase. Here, we purified Vip1 and Vip2 from B. thuringiensis and characterized the insecticidal effects of these protoxins. Bioassay results showed that a 1:1 mixture of Vip1Ad and Vip2Ag, purified by ion-affinity chromatography independently, exhibited insecticidal activity against Holotrichia parallela larvae, with a 50% lethal concentration value of 2.33 μg/g soil. The brush border membrane (BBM) in the midgut of H. parallela larvae was destroyed after feeding the Vip1Ad and Vip2Ag mixture. Vacuolization of the cytoplasm and slight destruction of BBM were detected with Vip2Ag alone, but not with Vip1Ad alone. Notably, Vip1Ad bound to BBM vesicles (BBMVs) strongly, whereas Vip2Ag showed weak binding; however, binding of Vip2Ag to BBMV was increased when Vip1Ad was added. Ligand blotting showed that Vip2Ag did not bind to Vip1Ad but bound to Vip1Ad-t (Vip1Ad was activated by trypsin), suggesting the activation of Vip1Ad was important for their binary toxicity. Thus, our findings suggested that Vip1Ad may facilitate the binding of Vip2Ag to BBMVs, providing a basis for studies of the insecticidal mechanisms of Vip1Ad and Vip2Ag.